Phytochemical Screening and Monitoring of Intercellular Changes in Murine Leydig Cells After the Treatment of Trigonella foenum-graecum L. Microgreens In Vitro - Jambor, T; Goc, Z; Zuscikova, L; Greifova, H; Kovacik, A; Kovacikova, E; Pec, M; Lukac, N (Physiological research, 2025)
The objective of our in vitro study was to quantify the biochemical profile where the total polyphenol, flavonoid and phenolic acid content was determined. The antioxidant potential of microgreen extract from Trigonella foenum-graecum L., was measured molybdenum reducing power assay. Specifically, the study assessed parameters such as metabolic activity (AlamarBlueTM assay), membrane integrity (CFDA-AM assay), mitochondrial potential (JC-1 assay), as well as reactive oxygen species generation (NBT assay). In addition, the steroid hormone release in TM3 murine Leydig cells after 12 h and 24 h exposures were quantified by enzyme-linked immunosorbent assay. The gained results indicate the highest value in total flavonoid content (182.59+/-2.13 mg QE) determination, supported by a significant (108.25+/-1.27 mg TE) antioxidant activity. The effects on metabolic activity, cell membrane integrity, and mitochondrial membrane potential were found to be both time- and dose-dependent. Notably, a significant suppression in reactive oxygen species generation was confirmed at 150, 200 and 250 microg/ml after 24 h exposure. In addition, progesterone and testosterone release was stimulated up to 250 microg/ml dose of Trigonella, followed by a decline in both steroid production at 300 and 1000 microg/ml. Our results indicate, that Trigonella at lower experimental doses (up to 250 microg/ml) may positively affect majority of monitored cell parameters in TM3 Leydig cells. Overleaf, increasing experimental doses may negatively affect the intracellular parameters already after 12 h of in vitro exposure. Key words Microgreens, Trigonella foenum-graecum L., Fenugreek, Leydig cells, Male reproduction.
Keywords: antioxidancia; Male; rostlinné extrakty; reaktivní formy kyslíku; Leydigovy buňky; vztah mezi dávkou a účinkem léčiva; mužské pohlaví; Trigonella; Leydig Cells; Reactive Oxygen Species; Animals; Plant Extracts; Antioxidants; zvířata; testosteron; myši; membránový potenciál mitochondrií; Mice; Dose-Response Relationship, Drug; Testosterone; Membrane Potential, Mitochondrial